Asymmetric Direct Michael Reactions of Cyclohexanone with Aromatic Nitroolefins in Water Catalyzed by Novel Axially Unfixed Biaryl-Based Bifunctional Organocatalysts - Zhao, Hong-Wu; Yang, Zhao; Yue, Yuan-Yuan; Li, Hai-Long; Song, Xiu-Qing; Sheng, Zhi-Hui; Meng, Wei; Guo, Xiao-Yu (Synlett, 2014)
A new family of axially unfixed biaryl-based water-compatible bifuctional organocatalysts were designed and synthesized for the asymmetric direct Michael reaction of cyclohexanone with various nitroolefins in water. One of the organocatalysts incorporates pyrrolidine and arylsulfonamide motifs as active organocatalytic sites, and axially unfixed biaryl as a skeleton; with this organocatalyst, the direct Michael reactions proceeded readily, furnishing the desired Michael adducts in high yields (up to 99% yield) with high levels of stereocontrol (up to >99:1 dr and 94% ee).
Keywords: biaryl compounds; aqueous chemistry; organocatalysts; asymmetric Michael reaction; stereoselectivity